The Role of Science in Postmodern Practice - Phillip Dybicz (Advances in Social Work, 2010)
Postmodern thought offers a critique to the heavily science-based approaches of the modernist discourse. Such critiques however tend to obscure the role that science has to play in postmodern practices. The current scientific-based modernist approaches faced this similar challenge when they arose in the early 1900s. In the 1800s, social agents did not base their interventions upon scientific authority, but rather, moral authority. While scientific knowledge displaced moral knowledge as the main guide for developing treatment plans, the field of social work did not abandon moral knowledge as useless. Instead, moral knowledge was transformed into a robust code of ethics—and serves the new role of circumscribing the boundaries within which one employs scientific knowledge. The postmodern discourse calls for this same displacement to occur—it seeks to have scientific knowledge circumscribe the boundaries within which an hermeneutic inquiry driven by a critical consciousness guides social work interventions.